Chirality evolution from sub-1 nanometer nanowires to the macroscopic helical structure - Zhang, Simin (2021)
The chirality evolution from the molecular level to the macroscopic level remains elusive for inorganic hierarchical structures. Without adding any chiral ligands or dopants, we prepared the macroscopic helical assemblies of sub-1 nm nanowires through a facile evaporation-induced self-assembly process with 100% efficiency, benefiting from the self-adjustment and self-recognition of sub-1 nm nanowires. Furthermore, we observed circularly polarized luminescence signals from the helical assemblies composed of nanowires and achiral organic fluorescent dyes, stemming from chirality transfer from the helical assemblies to achiral organic molecules. Molecular dynamics simulations found that the chirality of nanowires played a key role in the formation of macroscopic helical assemblies. Our work clarifies the chirality evolution and transfer of inorganic nanomaterials in part without being studied previously.